Analytic circuit model for thermal drying behavior of electronic inks - Maroli, Gabriel; Boyeras, Santiago; Giannetta, Hernan; Pazos, Sebastian; Gak, Joel; Oliva, Alejandro Raúl; Volpe, María Alicia; Julian, Pedro Marcelo; Palumbo, Felix (Frontiers in Electronics, 2023)
Understanding the sintering process of conductive inks is a fundamental step in the development of sensors. The intrinsic properties (such as thermal conductivity, resistivity, thermal coefficient, among others) of the printed devices do not correspond to those of the bulk materials. In the field of biosensors porosity plays a predominant role, since it defines the difference between the geometric area of the working electrode and its electrochemical surface area. The analysis reported so far in the literature on the sintering of inks are based on their DC characterization. The shape and distribution of the nanoparticles that make up the silver ink have been studied employing a transmission electron microscopy. Images of the printed traces have been obtained through a scanning electron microscope at different drying times, allowing to observe how the material decreases its porosity over time. These structural changes were supported through electrical measurements of the change in the trace impedance as a function of drying time. The resistivity and thermal coefficient of the printed tracks were analyzed and compared with the values of bulk silver. Finally, this work proposes an analytical circuit model of the drying behavior of the ink based on AC characterization at different frequencies. The characterization considers an initial time when the spheric nanoparticles are still surrounded by the capping agent until the conductive trace is obtained. This model can estimate the characteristics that the printed devices would have, whether they are used as biosensors (porous material) or as interconnections (compact material) in printed electronics.